Effect of water quality, magnetization and spraying with jasmonic acid on biochemical content of potato plants and tubers - Bassam Sh M Al-Asadi; Hayder S Jaafar; Mansoor A Aboohanah (International Journal of Medical Toxicology and Legal Medicine, 2024)
A field experiment was conducted for two consecutive spring seasons 2023-2024 in a private field in Al-Mahawil District (45 km) north of Babil Governorate to study the response of the potato plant, Synergy variety, to irrigation water type (River or drainage) treated magnetically and sprayed with jasmonic acid, in terms of potato plant content of some biochemicals. The experiment was a Split-Split Plot Design, R.C.B.D, 24 treatments with three replicates and 72 experimental units. Irrigation water quality (river or drainage) took the main plot, magnetization levels (1500 Gauss with contact path 38.5 cm2 * 1, 2, or 3 K) in sub plot and spraying with jasmonic acid (0, 15, 30) mg.L-1 was in sub-sub plot. The results of the experiment showed that river water at a level of 1.47 ds m-1 was significantly higher than drainage water in all studied characteristics. The positive effect also increased in magnetized water with contact path 38.5 cm2 * 3. A similar effect was recorded with spraying with jasmonic acid especially at a concentration of 30 mg L-1 compared to treatments sprayed at a lower concentration or control. The results showed that the interaction of river water 1.47 ds m-1 magnetized with a contact path of 38.5*3 cm2 and spraying with jasmonic acid 30 mg L-1 recorded the highest values ​​in the highest percentage of nitrogen, phosphorus and potassium in the leaves, the highest value of leaf total chlorophyll, and the highest percentage of tuber content of starch compared to plants irrigated with drainage water at a level of 5.7 ds m-1 that was not magnetized, regardless of presence or absence of spraying with jasmonic acid, which led to the lowest values.